The Influence of Liquidity, Leverage, and Firm Size on Tax Aggressiveness (An Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019–2023) - Siti Akhiria Ramadinah Putri; Ngatimin Ngatimin (Sean Institute, 2025)
This study explores the influence of liquidity, leverage, and firm size on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange. Tax aggressiveness is often seen as a corporate strategy to reduce tax liabilities through both legal and potentially borderline approaches. The research uses secondary data derived from annual reports and applies a purposive sampling technique to select companies that meet specific criteria. The analysis is conducted using panel data regression with multiple linear regression models, processed through EViews software. The findings reveal that liquidity and leverage do not have a significant impact on tax aggressiveness, indicating that companies with high or low liquidity and debt levels may not necessarily engage in aggressive tax planning. However, firm size demonstrates a negative and significant effect, suggesting that larger firms tend to be more compliant with tax obligations. The study contributes to a deeper understanding of the determinants of corporate tax behavior in developing economies.